(untitled) (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2014)
The impact of the teacher-student relationship on the child’s development proves to be particularly important in the first years of scholarization. Such impact is even higher in students with atypical development. Despite the clear relevance of the teacher-student relationship, researches have rarely encompassed subjects with special education requirements. The objective of this project, therefore, is to focus on the characteristics perceived by the teacher in the relationship with students with different educational needs. In particular, we describe the results achieved with different groups of children with special education needs, i.e. autism spectrum disorders (14) and Down’s syndrome (18), learning disorders (38) and attention-deficit and hyperactivity disorders (72). To measure the teacher’s perception of the quality of the relation with the pupil we have used the Italian version of the Student-Teacher Relationship Scale (STRS; Pianta, 2001) as developed by Fraire and colleagues (2013). The social bonds with children with difficulties differ for at least one relational aspect from those with children from the Control Group, the sole exception being children with Down’s syndrome. The Closeness dimension is hampered only in the case of the bonds with children affected by an autism spectrum disorder. On the contrary, relationships with children affected by frequent distraction and hyperactivism-related disorders are characterized by a higher level of Conflict and Dependency. Both dimensions increase in presence of high levels of pupil distraction, whereas only Conflict is at stake in presence of hyperactivity. As to children with learning disorders, only a difference in the Dependency dimension has been registered. These children, in fact, are seen by the teacher as being less autonomous than their classmates and thus requiring more frequent support and assistance.